Cav2.2 and Cav3.1 calcium channel inhibitors from Valeriana jatamansi Jones. Issue 72 (26th September 2017) - Jiang, He-Hai; Dong, Fa-Wu; Zhou, Jun; Hu, Jiang-Miao; Yang, Jian; Nian, Yin
Abstract : In China, the roots and rhizomes of Valeriana jatamansi Jones are traditionally used to treat gastrointestinal and rheumatic pain. In the present study, a number of N- and T-type calcium channel inhibitors were initially isolated and identified. Abstract : In China, the roots and rhizomes of Valeriana jatamansi Jones are traditionally used to treat gastrointestinal and rheumatic pain. Small molecule inhibitors of N-type (Cav 2.2) and T-type (Cav 3.1–3.3) calcium channels have become attractive resources in analgesic drug development. Therefore, in the present study, the isolated compounds (1–13 ) from V. jatamansi, including three new valepotriates (1–3 ), were initially evaluated on Cav 2.2 and Cav 3.1. As a result, compounds1–12 showed weak to potent inhibition on Cav 2.2 peak currents at 30 μM. Among them, compounds1, 6, 7, 11 and12 exhibited significant antagonistic effects, with EC50 values of 4.33, 2.18, 1.13, 2.70 and 7.8 μM, respectively. Meanwhile, the aforementioned compounds exhibited 18.2 ± 2.5% to 49.2 ± 7.1% peak current inhibition on Cav 3.1 at 30 μM. In addition, they also exhibited noticeable specificity against Cav 1.2, Cav 2.1, and KCNH2 (hERG) channels.